Islamic alternatives in mitigating disputes of debts in Islamic bankings: A comparative study between Islamic jurisprudence and Kuwait Law / Abdelkader Zenati - Abdelkader , Zenati (2022)
This research aims to find some legitimate alternatives for Islamic banks’ debt disposition on a jurisprudential level, such as sale or pledge of debt with the possibility of al- Muqassah or al-Hawalah; with trancing shari’ah roots of penalty clause which most banks use. The research problem lies in having clauses penalizing delays in the banks’ contracts, and banks’ rigidity in some of their funding modalities which are similar to the usurious instalments, then Islamic banks resort to positive law which, based on the study of the civil law, might differ from the Islamic legislation and might contradict the specificities of Islamic banks who must commit to the rulings of Islamic shari’ah in settling conflicts. The significance of this research is therefore presented in bringing Islamic banks to the forefront in dealing with their issues while maintaining their specificities so that they remain the best and safest option among their conventional counterparts. The descriptive analytical method is used by describing the transactions, their meanings and modals based on Quran, Sunnah, and the opinions of the jurists and civil law experts. The research also carried a financial analysis of the two most important Islamic banks (Kuwait Finance House, and Al-Rajihi Bank). Deductive approach was used as well to derive the most significant models that can be based on to the application of the deposition of debts as a means of solving financial disputes. comparative method was used by comparing between the Islamic jurisprudence and Kuwaiti civil law. Among the significant results that have been reached is that there are numerous alternatives of the penalty clause, and that the aforementioned legitimate alternatives have been examined in terms of the agreement or disagreement between the jurists regarding their legitimacy, while choosing the opinions which bring ease to people and considering the opinions of the doctrines that use the principles of sad al-dara’I’ and accusation in financial transactions to avoid riba and modalities that eventually lead to it. The research also concluded that the Kuwaiti civil law is compatible with the Islamic shari’ah in many legal provisions while it disagrees in others. The compatibility of other provisions in Kuwaiti civil law with Islamic shari’ah has not yet been examined, such as differentiating between selling debt to the debtor and selling it to other parties. Such loopholes might be used to circumvent the rulings and eventually fall in riba or cause harm to the other party of the conflict. Therefore, the researcher recommends treating many cases which the civil law addressed in broad terms and focusing more on generating solutions for the financial issues between Islamic banks nd debt burdened clients, especially with the occurrence of many calamities, such as earthquakes and fires that affect industrial and agricultural enterprises; also, the emergence of pandemics such as the Covid-19.